Behavioral governance and firm returns in the digital banking ERA: The role of CEO overconfidence, risk-taking, and CEO characteristics - evidence from Indonesia - Mardjono, Amerta; Maupa, Haris; Setyawan, Ignatius Roni (Edelweiss Applied Science and Technology, 2026)
This study examines behavioral corporate governance in Indonesia’s digital banking sector by analyzing how CEO overconfidence influences firm returns through risk-taking behavior, while considering CEO age and gender as moderating governance mechanisms. Grounded in Upper Echelons Theory and Agency Theory, the study employs a quantitative approach using Structural Equation Modeling (SEM) to analyze 196 firm-year observations from seven Indonesian digital banks over the period 2018–2024. The results demonstrate that CEO overconfidence significantly increases risk-taking behavior, while risk-taking positively affects firm returns. CEO overconfidence does not exert a direct effect on firm returns, indicating that its economic impact materializes indirectly through strategic risk-taking decisions. CEO age significantly moderates the relationship between overconfidence and risk-taking, attenuating excessive risk escalation, while both CEO age and gender positively moderate the relationship between risk-taking and firm returns. These findings suggest that executive demographics function as behavioral governance filters that shape how managerial bias is translated into financial outcomes. This study reframes corporate governance as a behavioral system by integrating executive psychology and demographic heterogeneity into the governance–performance nexus. By providing emerging-market evidence from Indonesia’s digital banking sector, the study demonstrates that firm returns depend not on executive optimism per se, but on how behavioral bias is governed through risk discipline and leadership composition in technology-driven financial institutions.